DISCLOSURE OF CASH RECEIPT AND EXPENDITURE OF BAITUL MAAL HIDAYATULLAH D.I YOGYAKARTA REPRESENTATIVE AS A GRASS ROOT ENTITY FOR THE ECONOMIC EMPOWERMENT OF PESANTREN IN THE NEW NORMAL ERA - Mila Alim Bachri (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2020)
Baitul Maal Hidayatullah Yogyakarta is considered a grass-root entity that has an obligation to provide stimulus during the pandemic and improve the welfare of its members during the Covid-19 pandemic. The financial reports in order to increase credibility and its role must be maximized. The research will have the aim of knowing the application of the internal control system in the cash receipt and cash disbursement cycle and identifying the weaknesses and strengths that have been implemented. This study used a descriptive research method using a factual approach and also journals as literature and conducting observations and analysis at the Baitul Maal Hidayatullah Yogyakarta and conducted a qualitative study. The results of the study measured 5 aspects of the application of internal control in the cycle of cash receipts and disbursements according to COSO at the Baitul Maal Hidayatullah Yogyakarta, namely 1) control environment, 2) risk assessment, 3) control activities, 4) information and communication and 5) monitoring. From these results, it is concluded that the implementation of the internal control system in the cash receipt and cash disbursement cycle of the Baitul Maal Hidayatullah Yogyakarta Mosque has been going well, in line with the identified strengths and weaknesses. Weakness points such as managing using basic applications can potentially be developed further.